Five-decade-delayed closed flexor tendon rupture due to Galeazzi dislocation fracture associated with Behçet syndrome: A case report. (2018) - Ohara, Masato; Oda, Ryo; Toyama, Shogo; Katsuyama, Yusei; Fujiwara, Hiroyoshi; Kubo, Toshikazu
Highlights: Delayed flexor tendon rupture after Galeazzi dislocation-fracture is unusual. Even minimal capsule damage can influence tendon degeneration. Corticosteroid usage or a collagen disease may contribute to tendon sensitivity. Even minimal past trauma-related damage is vital in sensitive cases. Abstract: Introduction: Closed flexor tendon rupture after a malunited distal radius fracture is rare and usually becomes apparent early after the fracture. Most cases are accompanied by a severe distal radio-ulnar joint capsule injury, wherein bone protrusion (as a spur) directly stresses the tendons. We experienced a nonspecific flexor tendon rupture associated with an old fracture and the presence of collagen disease. Presentation of case: A 63-year-old woman presented with delayed complete rupture of the flexor digitorum profundus (FDP) of the fifth digit. Her history included closed fracture on the left wrist at age 13 years. At 27 years, she was diagnosed with Behçet syndrome and commenced oral prednisolone 10 mg/day. At the current admission, physical examination revealed that she was incapable of fifth finger flexion after minor passive extension. The fifth digit FDP rupture appeared to be due to damage at the wrist-level fracture site. A tiny capsule rupture was seen on the volar side of the distal radio-ulnar joint. We resected ulnar head osteophytes protruding from the capsule hole and transferred tendon from the fifth FDP to the fourth FDP. Conclusion: Reportedly, metalloproteases weaken tendon structure by acting as a collagenase in patients with Behçet syndrome. Also, vasculitis next to a tendon and steroid intake are considered to impede the tendon repair process. Hence, even minor trauma may lead to complete tendon rupture. Although an injury seems slight, we should take into account the possible history of bone and joint trauma.